Effect of Intravenous Oxycodone in Combination With Different Doses of Dexmedetomdine on Sleep Quality and Visceral Pain in Patients After Abdominal Surgery: A Randomized Study. Issue 12 (December 2018) - Jiang, Zongming; Zhou, Guozhong; Song, Qiliang; Bao, Chenying; Wang, Hua; Chen, Zhonghua
Abstract : Objective: Oxycodone or dexmedetomidine (DEX) alone are widely used in clinical practice. The aim of this study was to observe the effect of 2 oxycodone and DEX combinations on postoperative sleep quality. Methods: This was a prospective and randomized clinical study. A total of 99 patients underwent laparoscopic-assisted operations on stomach and intestines with general anesthesia were enrolled and randomly divided into 3 groups according to postoperative analgesic protocol (n=33 each). The analgesic protocols were as follows after the surgery. In group C, 0.6 mg/kg oxycodone alone was diluted to 100 mL in 0.9% saline. In group D1 or D2, 0.6 mg/kg oxycodone combined with 2.4 μg/kg or 4.8 μg/kg DEX was diluted to 100 mL in 0.9% saline, respectively. The intravenous patient-controlled analgesia device was set up to deliver a continuous infusion of 3 mL/h and a bolus of 1 mL, with a 12-minute lockout interval. The primary outcome was the percentage of stage 2 nonrapid eye movement (stage N2) sleep. Polysomnography was performed the night before operation (PSG-night0), the first (PSG-night1) and second (PSG-night2) nights after surgery. Results: A total of 97 patients were included in the final analysis. Compared with group C, N2 sleep were higher in groups D1 and D2 on PSG-night1 (54±9% and 53±10%, respectively) and PSG-night2 (55±7% and 56±8%, respectively) ( P <0.001 for all comparisons). No differences were observed regarding N1 and N2 sleep between groups D1 and D2 on PSG-night1 and PSG-night2 ( P >0.05). Group C had higher percentage of N1 sleep on PSG-night1 (37±5%) and PSG-night2 (33±3%) when compared with groups D1 and D2 ( P <0.001 for the comparisons). Groups D1 and D2 required lower rates of rescue analgesia (5% and 4.7%, respectively; P =0.012) and effective pressing times (10.7±4.8 times and 9.9±2.6 times, respectively; P <0.05) when compared with group C, whereas no statistical significance was found between groups D1 and D2 . Furthermore, there were no significant difference about resting visual analogue scales at 4, 6, and 12 hours postoperatively between groups D1 and D2 . In comparison with the other 2 groups, group D2 had a higher occurrence of postoperative hypotension (24.2%) ( P <0.05), though without significant sinus bradycardia. Discussion: DEX combined with oxycodone can improve sleep quality and provide good visceral analgesia. However, larger doses of DEX does not further improve sleep but increases the risk of hypotension.